2001
DOI: 10.1002/ccd.1152
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of coronary angiography using 4F catheters: 4F manual versus “Acisted” power injection technique

Abstract: Compared with 6F catheters, diagnostic coronary angiographic and ventriculographic images with 4F catheters can be obtained with equivalent results using less radiographic contrast volume. Whether 4F coronary angiography would be superior using a power-assisted, operator-controlled technique compared with manual technique is unknown. To determine whether 4F coronary angiography using operator-controlled power injection (Acist, Minneapolis, MN) was equivalent or superior to the 4F manual technique, 96 unselecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
(15 reference statements)
1
6
1
Order By: Relevance
“…Two studies are a continuation of each other, the only difference being 5 additional patients included in the manual injection group. (4, 7) However, after excluding the second study with 5 additional patients, we determined that there were still statistically significant lower volumes of contrast administered for diagnostic catheterizations. Second, the nature of the studies do not allow for equipoise or blinding; 2 studies report randomization techniques, 1 of which employed a faulty strategy, and none report withdrawal or dropout rates, creating an overall low Jadad score (Table 2).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Two studies are a continuation of each other, the only difference being 5 additional patients included in the manual injection group. (4, 7) However, after excluding the second study with 5 additional patients, we determined that there were still statistically significant lower volumes of contrast administered for diagnostic catheterizations. Second, the nature of the studies do not allow for equipoise or blinding; 2 studies report randomization techniques, 1 of which employed a faulty strategy, and none report withdrawal or dropout rates, creating an overall low Jadad score (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…(4, 6-8) One study concluded no difference in the amount of contrast volume delivery, while 3 reported significantly less contrast volume use when using the 4F automated injection compared with manual technique. (4, 6, 7) Overall, 5.53 ml (p = 0.01, 95% CI, -9.91, -1.16) less contrast was delivered in the ACIST group compared to the manual group employing automated injectors for left ventriculography only. However, our meta-analysis does not have the ability to explore the causal role of catheter size on contrast volume or CIN endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, angiographic quality also decreased [20]. It was reported in 2001 that 4-Fr angiography with the ACIST power injector resulted in image quality similar to that with 4-Fr manual injection technique with significantly reduced contrast medium usage [21]. Thus, the combination of catheter down-sizing with power injector use is effective in reducing the amount of contrast medium delivered without reducing angiographic quality.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, there is a continued effort to reduce vascular complications and the amount of contrast used, and to reduce procedure length and time to postprocedure ambulation, while maintaining excellent image quality [1–3]. Data are not conclusive regarding the potential advantage of smaller diagnostic catheter use for cardiac angiography in relation to the aforementioned parameters [8–13].…”
Section: Introductionmentioning
confidence: 99%